2012
DOI: 10.1093/humrep/des394
|View full text |Cite
|
Sign up to set email alerts
|

Sequential comprehensive chromosome analysis on polar bodies, blastomeres and trophoblast: insights into female meiotic errors and chromosomal segregation in the preimplantation window of embryo development

Abstract: These findings provide critical insights into the mechanisms causing errors during female meiosis and the preimplantation embryo development period to improve the design and treatment outcome of PGS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
122
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(135 citation statements)
references
References 15 publications
8
122
3
2
Order By: Relevance
“…When FISH was compared to CCS, it was found that mosaicism was three times more common in FISH [35]. When compared to polar body biopsy it was found that blastomere biopsy with CCS was very accurate (94.2 %) when compared to trophoectoderm biopsy with CCS [3]. These findings support analysis of cleavage-stage biopsy with CCS techniques such as SNP or CGH, so that PGS could still be utilized with fresh-embryo transfer.…”
Section: Introductionmentioning
confidence: 72%
“…When FISH was compared to CCS, it was found that mosaicism was three times more common in FISH [35]. When compared to polar body biopsy it was found that blastomere biopsy with CCS was very accurate (94.2 %) when compared to trophoectoderm biopsy with CCS [3]. These findings support analysis of cleavage-stage biopsy with CCS techniques such as SNP or CGH, so that PGS could still be utilized with fresh-embryo transfer.…”
Section: Introductionmentioning
confidence: 72%
“…All inconsistencies (five embryos) were attributable to chromosomal/ segmental copy number mosaicism in the ICM or TE. Embryonic mosaicism is derived from a variety of mechanisms including chromosome anaphase lagging (Coonen et al 2004, Capalbo et al 2013a, nondisjunction (Bean et al 2001) or endoreplication.…”
Section: Discussionmentioning
confidence: 99%
“…The initial diagnosis obtained by aCGH was performed by a commercial reference laboratory according to the manufacturer's protocol (BlueGnome) and as previously described. 20 The second …”
Section: Genetic Testing Methodsmentioning
confidence: 99%